2012
DOI: 10.1021/jz301294q
|View full text |Cite
|
Sign up to set email alerts
|

Dry Deposition of Biogenic Terpenes via Cationic Oligomerization on Environmental Aqueous Surfaces

Abstract: The products we observe are produced when the gaseous terpenes collide with the intact electroneutral aqueous jets as they emerge from the nozzle, i.e., before jets are broken up by the nebulizer gas. Since mass spectrometers detect net charge, the first step is the separation of pre-existing anions from cations in the electroneutral inflowing solutions. This is accomplished via the pneumatic breakup of the aqueous jet by a fast nebulizer gas that shears the outermost jet layers into droplets carrying net char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
82
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 54 publications
13
82
2
Order By: Relevance
“…The species produced on the surface of such jets are analyzed in situ via online ES-MS. The present experimental setup essentially is the same as the one reported elsewhere (62,64,65). Solutions are pumped (100 μL·min −1 ) into the spraying chamber through a grounded stainless steel needle (100-μm bore) coaxial with a sheath-issuing nebulizer N 2 (g) at a high gas velocity v g (∼160 m/s).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The species produced on the surface of such jets are analyzed in situ via online ES-MS. The present experimental setup essentially is the same as the one reported elsewhere (62,64,65). Solutions are pumped (100 μL·min −1 ) into the spraying chamber through a grounded stainless steel needle (100-μm bore) coaxial with a sheath-issuing nebulizer N 2 (g) at a high gas velocity v g (∼160 m/s).…”
Section: Methodsmentioning
confidence: 99%
“…We exploited the high sensitivity, surface selectivity, and unambiguous identification capabilities of a newly developed instrument based on online electrospray mass spectrometry (ES-MS) (58)(59)(60)(61)(62) to identify the primary products of reactions R1-R4 on aqueous FeCl 2 microjets exposed to gaseous H 2 O 2 and O 3 beams under ambient conditions [in N 2 (g) at 1 atm at 293 ± 2 K]. Our experiments are conducted by intersecting the continuously refreshed, uncontaminated surfaces of free-flowing aqueous microjets with reactive gas beams for τ ∼10-50 μs, immediately followed (within 100 μs; see below) by in situ detection of primary interfacial anionic products and intermediates via ES-MS (Methods, SI Text, and Figs.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17][18][19] Data analysis based on mass balances and the kinetic theory of gases suggest that the thickness of the interfacial layers sampled in these experiments is less than a few nm, most likely below 1 nm. 9 More compellingly, we recently showed that the depth of the interfacial layers sampled in our experiments is controllable as a function of nebulizer gas velocity v g .…”
mentioning
confidence: 86%